Pengaruh E-servicescape Online Marketplace Shopee pada Perceived Value dan Kepuasan Pelanggan, serta Dampaknya terhadap Loyalitas Pelanggan - Marsha Karina (Jurnal Maksipreneur, 2019)
Online marketplace business competition is getting tougher, so customer loyalty is becoming an increasingly important factor for companies. Shopee is one of the increasingly popular online marketplace business in Indonesia. Customer loyalty can be rised through increasing the number of transactions and visits on the Shopee website. E-servicescapes are all elements that companies use to deliver digital services to consumers. The elements of e-servicescapes include aesthetic appeals, layout and functionality, and financial security. The level of customer satisfaction and perceived value of e-servicescapes can increase customer loyalty which have an impact for increasing the number of visits to Shopee's website. The purpose of this study is to determine the e-servicescape elements that most influence the satisfaction and perceived value of Shopee website users. This study used a quantitative approach with primary data derived from Shopee website users. An important contribution of this research is the guideline to improve the quality of e-servicescapes, so that the company is able to get a higher level of customer loyalty. The results of this study indicate that e-service-scapes affect the perceived value and customer satisfaction that can encourage the formation of their loyalty. Other findings show that Shopee has financial security as the best e-servicescape aspect. However, Shopee still needs improvements in the aspects of layout and functionality, because these aspects get the lowest ratings from Shopee website users.